FINANCIAL TECHNOLOGY AND DEMOGRAPHIC FACTORS ON WELFARE ANALYSIS - Agustin, Grisvia; Abbas, Muhammad Hasyim Ibnu; Dwiputri, Inayati Nuraini; Prastiwi, Lustina Fajar (Faculty of Economics and Business, Hasanuddin University, 2022)
Financial technology is very useful in facilitating financial transactions worldwide. It was created to make getting funds and managing finances easier, which can improve people’s welfare. However, it also poses a threat in the form of loans from financial technology lending companies that are not licensed and illegally operate so that customers can be bound by huge interest rates and terrorized by debt collectors. Therefore, this study aims to analyze literacy about financial technology and demographic factors that affect welfare. The analysis results show that most respondents are still ignorant or do not understand the benefits of fin-tech for improving their welfare, and the respondents’ welfare is only affected by age. Although 92% of respondents have savings, these savings do not use fin-tech. Fin-tech is still seen as something that plunges like a shark loan trap, so most respondents still avoid fin-tech for their financial management. Respondents still do not use fin-tech optimally and urgently need education and socialization related to fin-tech.